Difusão do prontuário eletrônico do cidadão da estratégia e-SUS AB em equipes de saúde da família - Grazielly Soares Avila (2020)
Over the past decade, we have witnessed the profusion of initiatives by the Ministry of Health, focused on strengthening the infrastructure of Primary Care in Brazil and improving the quality of health information. One of those initiatives was the creation of the e-SUS AB Strategy, which has two software systems, the Simplified Data Collection (CDS) and the Electronic Citizen's Record (PEC). The aim of this study was to analyze the diffusion of PEC and its influence on Care Management in Family Healthcare teams. A single case study was carried out, with a qualitative approach, using Everett Rogers' Diffusion of Innovation Theory as a theoretical framework. The study was carried out in the counties of Mathias Lobato and Engenheiro Caldas in Minas Gerais, with 39 health professionals, through interviews and direct observation. Data analysis was performed using Content Analysis, Thematic-Categorial modality and systematized using the MaxQDA software. The results were organized into three categories. In category I “PEC Innovation and its attributes”, the participants reported the following advantages: the practicality in making production reports, made by the system; more accurate data with the launch in real time; saving resources and the possibility of correcting typing errors. As disadvantages: the inability to flag typos; the inability to edit some data; the disappearance of registrations and the general access to the micro areas in the PEC territory module. In the Compatibility attribute, we identified that the PEC provides agility, accelerates the production of professionals and increases access to data and patient history. Among the incompatibilities, we identified the lack of information considered important and necessary by professionals; the persistence of using paper records; the difficulty of visualizing health situations in the territory; internet failures and low quality of tablets. In the Experimentation attribute, it was noticed that there was no time for experimentation before the PEC implementation. In the Observability attribute, the reduction of problems with the legibility of the prescriptions was identified as a positive result, and the loss of time with the filling of information and the increase in the service time as negative results. In the Complexity attribute, we identified that the main difficulty found is linked to the volume of mandatory information to be filled out in the PEC and the repetition of the information. In the second category “Communication Channels, Time and Social System: influences on the dissemination of the PEC” we know the communication channels involved in the diffusion of the PEC, namely: interpersonal communication, the telephone, the Whatsapp and the internet, being communication interpersonal the main channel used. In the Time dimension, it was evident that the PEC was implemented suddenly, with no time for experimentation, through a normative decision from the federal level. In the Social System dimension, the components of this system and their respective structures, formal and informal, were identified, namely: the Ministry of Health, the City Hall, the Municipal Health Secretariat, ESF professionals and key informants, the latter being key in the process of implementing the PEC. In the third category “PEC influences on Care Management”, we identified influences in three of the six dimensions: professional, organizational and systemic. We conclude that the adoption of the PEC constitutes a great challenge for ESF professionals and for the management spheres. We also concluded that the Care Management in AB has gained important support from the PEC, which materializes as a tool that contributes to Care Management in AB.